A Clinical Study To Evaluate The Efficacy Of Palasha Kshara Sutra In The Management of Bhagandara w.s.r. To Fistula In Ano. - Sharma, Shipra; Ankita; Raina, Sorabh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Bhagandara is a common disease of ano-rectal area. According to Acharya Sushruta, ‘bhagandara’ starts as deep-seated pidika (boil) surrounding the guda (anus) within two angulas perimeter, producing fever and pain. The signs & symptoms of Bhagandara closely resemble with the disease Fistula-in-ano. Fistula-in-ano is a communicating track lined by morbid granulation tissue linking two epithelial lined surfaces in the ano-rectal area. It is one of the most obnoxious condition for the patient and a challenge for the medical fraternity due to its peculiar site of occurrence. Conventional choice of treatment is ano-rectal surgery. Many complications viz itching, swelling, pain, recurrence, infection may occur following ano-rectal surgery. Whereas, Ayurvedic treatment i.e. Ksharasutra threapy is much more cost-effective and with least complications. The present study was conducted on 20 patients of Bhagandara to evaluate the effectiveness and suitability of Palasha Ksharasutra in the management of Bhagandara (fistula in ano). The therapy showed encouraging results in all the parameters of Bhagandara viz pus discharge, pain, healing time with no complications. It is more economical and readily available throughout the year.